Seasonal activity and basking of the southernmost population of the freshwater turtle Phrynops hilarii (Chelidae) - Semeñiuk, María Belén (2017)
This study focuses on basking behaviour of Phrynops hilarii in the southernmost population of the species’ range. The objective was to determine how environmental features affect the basking behaviour of the species. We analyzed two years of data on the seasonal activity of the species for the same stream. We detected 389 P. hilarii basking, mostly alone (76.8%), and on logs and branches (79.3%), but large turtles used shorelines more frequently than did smaller turtles. Basking peaked during late winter and early spring. We found no correlation between the number of basking turtles and air, substrate or water temperatures. P. hilarii was active through all seasons, with activity peaking in summer, when temperature is highest but basking frequency is low. Type of substrate, time of day, and season are key factors that influence the basking behaviour of P. hilarii.